Relationship between bulk foam stability, surfactant formulation and oil displacement efficiency in porous media. (1st September 2017) - Osei-Bonsu, Kofi; Grassia, Paul; Shokri, Nima
Graphical abstract: Highlights: Oil displacement by foam was investigated in a 3D printed porous medium. Oil displacement by foam is strongly influenced by the surfactant formulation. No correlation between bulk foam stability and displacement efficiency was observed. Stability of foam at bulk scale does not determine its effectiveness in porous media. Abstract: Success of foam as a displacing fluid in porous media depends on longevity of foams in the presence of non-aqueous phase liquids such as hydrocarbons. The stability of foam at bulk scale has been used in many cases to screen potential surfactants for core flooding studies. Although this method may aid in determining the foamability and stability of a surfactant, no reliable correlation has been found to exist between bulk foam stability and performance in porous media. We have conducted a comprehensive series of experiments to examine and compare the stability of selected surfactant foams at bulk scale and during oil displacement in porous media. The oil displacement was investigated in a micromodel manufactured by 3D printing technology. Our results demonstrated that oil displacement efficiency by foam is strongly influenced by the surfactant formulation. More importantly, no meaningful correlation between the bulk foam stability and the oil displacement efficiency of the corresponding foams in porous media was observed. Our pore-scale investigation shows that the stability or instability of foam at bulk scale does not necessarily determine its effectiveness in porous media. Hence, performing displacement tests as presented in our study may give more insights into the potential performance of foams.